Ready access to end-functional polystyrenes via a combination of ARGET ATRP and thiol–ene chemistry1. Issue 39 (21st October 2015) - Altintas, Ozcan; Josse, Thomas; De Winter, Julien; Matsumoto, Nicholas M.; Gerbaux, Pascal; Wilhelm, Manfred; Barner-Kowollik, Christopher
<x xml:space="preserve">Abstract</x> Bromine end-groups of ATRP polystyrenes were converted into terminal alkene groups via a facile synthetic strategy. Subsequently, a light-induced radical thiol–ene reaction was employed for the functionalization of the terminal double bonds.